ROLE OF UTTARVASTI IN THE MANAGMENT OF VANDHYATVA (TUBAL BLOCK)-A CASE STUDY - MeenaHR; Vandhana (International Journal of Applied Ayurved Research, 2018)
Ayurveda is a branch of medicine which has served humanity since ancient time by both preventive and curative aspects. According to Ayurveda, childlessness is described as vandhyatva and is termed as infertility in the modern science. Among all health problems infertility is one of main issue in today’s life. Nearly 10-14% of individual’s belongings to the reproductive age group are affected by infertility. The rate of infertility is steadily increasing due to change in life style, high pollution, socioeconomic cause and enormous amount of stress. Ayurveda explained wide range of protocols and medicines for the management of Vandhyatwa, out of which role of Uttarabasti in a single case diagnosed with Right complete fallopian tube block was observed. It had given encouraging result with patent tube after 3 consecutive cycles of treatment.